Biomass production and leaf nutrient content in Justicia pectoralis Jacq. with different types of fertilization (Research, Society and Development, 2020)
The objective of this work was to evaluate different sources of fertilization in the growth of the plant, accumulation of nutrients in the leaves of Justicia pectoralis Jacq. aiming at improving biomass production. The treatments consisted of three different fertilizations: organic (poultry manure), chemical and organomineral, plus the control (without fertilization), arranged in a randomized block design, with 18 repetitions per treatment in four blocks. At 100, 120, 150 and 180 days after transplantation, height and diameter were determined in ten plants in the useful area of ​​each plot. In the last evaluation, the plants were harvested manually. Shoot biomass (g) and leaf nutrient content were evaluated. The statistical program used was Sisvar, and the data obtained were subjected to analysis of variance. The regression analysis was used for the biometric data of the plants and for the mineral concentration the averages were compared by the Tukey test (p Ca> K> Mg> P> S; and for micronutrients (mg Kg-1): Fe> B> Mn> Zn> Cu. There was a positive influence of different fertilizations on plant growth in height, diameter and dry biomass, and organomineral fertilization provided greater plant development. Because it is a plant with a diversity of secondary metabolites and belonging to the flora of the Cerrado Biome, scientific research is still necessary to enable the production in scale avoiding extraction and loss of genetic material.